Optimization of processing technology for blue honeysuckle berry snack: From microwave vacuum concentration to freeze‐drying. Issue 2 (14th December 2020) - Zhao, Yueming; Zhang, Yuhan; Zhu, Yong; Liu, Chai; Feng, Shaoxuan; Ma, Wenyu; Gao, Ming; Zheng, Xianzhe
Abstract: To enrich the berry product variety and improve the edible quality of blue honeysuckle berry (BHB), on the basis of determining the mixture recipe of the BHB pulp, fructose, and yoghurt (BHBY), the combined technology of microwave vacuum concentration (MVC) and freeze‐drying (FD) was proposed to produce novel BHBY snack. The results showed that the highest retention rate of anthocyanin content was 94.83% under a vacuum pressure of −0.05 MPa and a temperature of 50°C. The optimal FD parameters for the concentrated BHBY were determined as critical moisture content of 1.89 g/g (dry basis), material thickness of 13 mm, and desorption temperature of 36.9°C with a snack of hardness of 1, 943.9 g, brittleness of 604 peaks, L * value of 36.7, and a * value of 20.7. The final BHBY snack presents acceptable taste with crispy texture and desired color. The developed processing technology is feasible for BHB snack. Practical applications: This work developed a novel BHB snack by the application of MVC followed by FD technology and optimized the processing technology to achieve the desired product with high drying efficiency, preferable texture taste, and considerable retention of anthocyanin content. The recipe of BHBY and the processing technology proposed was beneficial for improving the edible quality of BHB. Further, it may provide guidance for the development of novel snack and deep processing of berry fruits like BHB.